Metabolic and transcriptional alternations for defense by interfering OsWRKY62 and OsWRKY76 transcriptions in rice - Xiaoxing Liang (Nature Portfolio, 2017)
Abstract Metabolomic and transcriptomic approaches were used to dissect the enhanced disease resistance in the plants harbouring a RNA interfering construct of OsWRKY62 and OsWRKY76 (dsOW62/76) genes. The primary metabolic pathways were activated in dsOW62/76 compared with wild-type (ZH17) plants, revealed by increased accumulation of amino acids and constituents of citric acid cycle etc. Contents of phenolic acids derived from phenylpropanoid pathway were elevated in dsOW62/76 plants. Importantly, phenolamides, conjugates of the phenolic acids with amines, were detected in large number and mostly at higher levels in dsOW62/76 compared with ZH17 plants; however, the free pools of flavonoids were mostly decreased in dsOW62/76. Salicylic acid (SA) and jasmonic acid (JA)/JA-Ile contents were increased in dsOW62/76 and knockout lines of individual OsWRKY62 and OsWRKY76 genes. Transcription of isochorismate synthase (OsICS1) gene was suppressed in dsOW62/76 and in MeJA-treated rice plants, whereas the transcription level of cinnamoyl-CoA hydratase-dehydrogenase (OsCHD) gene for β-oxidation in peroxisome was increased. The calli with OsCHD mutation showed markedly decreased SA accumulation. These results indicate that OsWRKY62 and OsWRKY76 function as negative regulators of biosynthetic defense-related metabolites and provide evidence for an important role of phenylpropanoid pathway in SA production in rice.